2009
DOI: 10.2190/wr.14.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Developing a New Measure of Work Alienation

Abstract: There is limited research on work alienation in contemporary management studies. One of the possible reasons is the lack of a parsimonious and validated measure of work alienation. The present study reports the construction and evaluation of a new scale for measuring work alienation, in the interest of facilitating further research in this area and aiding the detection and assessment of worker alienation, providing cues to which management should pay attention for any consequent correction, if needed. In Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(143 citation statements)
references
References 48 publications
4
116
0
6
Order By: Relevance
“…The alienation was assessed using the eight-item Work Alienation Scale (Nair & Vohra, 2009) (i.e. "I do not feel connected to the daily events in my workplace").…”
Section: Anonymity Of the Respondents Was Assuredmentioning
confidence: 99%
“…The alienation was assessed using the eight-item Work Alienation Scale (Nair & Vohra, 2009) (i.e. "I do not feel connected to the daily events in my workplace").…”
Section: Anonymity Of the Respondents Was Assuredmentioning
confidence: 99%
“…It was studied and discussed across several subjects such as theology, philosophy, sociology, psychology, and psychiatry (Nair & Vohra, 2009). Karl Marx (1844/1961 was the first author that developed the concept of work alienation .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers (Banai, Reisel, & Probst, 2004;Hirschfeld & Feild, 2000) have tended to return to the unidimensional conceptualization of work alienation (Nair & Vohra, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous DRIVERS AND OUTCOMES OF WORK ALIENATION 3 research has reported that alienation is inversely related to a handful of these work characteristics (e.g., Banai & Reisel, 2007;Banai, Reisel, & Probst, 2004), these studies have either used a multidimensional measure of alienation, or a measure of alienation that is too broad in focus. In the present study, a validated, uni-dimensional measure of alienation is used (Nair & Vohra, 2009). Moreover, no other study, to our knowledge, has simultaneously assessed these four precursors of alienation.…”
mentioning
confidence: 99%